2011
DOI: 10.1186/1742-4933-8-4
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory and Immunological parameters in adults with Down syndrome

Abstract: BackgroundThe increase in life expectancy within the general population has resulted in an increasing number of elderly adults, including patients with Down syndrome (DS), with a current life expectancy of about 50 years. We evaluate the parameters of humoral and cellular immune response, the quantitative expression of the regulator of calcineurin1 gene (RCAN1) and the production of cytokines. The study group consisted of adults DS (n = 24) and a control group with intellectual disability without Down syndrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 51 publications
(54 reference statements)
5
41
0
3
Order By: Relevance
“…While the clinical presentation of Down’s is complex and variable, characteristic features such as progressive mental deterioration, increased risk for autoimmune disease, and early onset Alzheimer disease support the hypothesis that Down’s syndrome is associated with premature aging and abnormalities in the innate immune response [27]. Early genetic and bioinformatics analysis suggested that much of the developmental pathology of Down’s syndrome can be attributed to the extra chromosome 21 ‘gene dosage’ effect, resulting from the 50% increase in expression of the ~300 chromosome genes, that leads to an imbalance of critical gene expression, which in turn initiates the Down’s phenotype [23]. More current genetic evidence suggests that the Down’s phenotype is most likely multi-genetic, and only a specific subset of the 300 or so trisomic genes, interacting with other disomic genes, mediates disease onset [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…While the clinical presentation of Down’s is complex and variable, characteristic features such as progressive mental deterioration, increased risk for autoimmune disease, and early onset Alzheimer disease support the hypothesis that Down’s syndrome is associated with premature aging and abnormalities in the innate immune response [27]. Early genetic and bioinformatics analysis suggested that much of the developmental pathology of Down’s syndrome can be attributed to the extra chromosome 21 ‘gene dosage’ effect, resulting from the 50% increase in expression of the ~300 chromosome genes, that leads to an imbalance of critical gene expression, which in turn initiates the Down’s phenotype [23]. More current genetic evidence suggests that the Down’s phenotype is most likely multi-genetic, and only a specific subset of the 300 or so trisomic genes, interacting with other disomic genes, mediates disease onset [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Trotta et al (2011) reported a spontaneous increase in the production of IFN-γ, TNF-α, and IL-10 in adult patients with DS. Nateghi Rostami et al (2012) found high levels of TNF-α and IFN-γ and low levels of IL-10 in patients with DS.…”
Section: Discussionmentioning
confidence: 99%
“…Some characteristics of cytokine production in patients with DS have been described (Shimada et al 2007;Trotta et al 2011;Nateghi Rostami et al 2012 DOL, day of life; TNF-α,tumor necrosis factor α; GM-CSF, granulocyte-macrophage colony-stimulating factor; G-CSF, granulocyte colony stimulating factor; MCP-1, monocyte chemotactic protein 1; MIP-1β, macrophage inflammatory protein 1β. a The unit of concentration of cytokines, chemokines and growth factors is all pg/mL in this Table. b The control group included 8 newborn patients who were admitted to the NICU with various risks.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the onset and the progression of CNS disease states is often characterized by deregulation of systemic and CNS-specific T- and B-cells and microglia, CNS resident mononuclear phagocytes, and associated inflammatory cascades [25-30]. One particularly intriguing study recently highlighted the importance of proper microglial functioning in the brain.…”
Section: Neuroimmune Interactionsmentioning
confidence: 99%